Ebola virus VP35 NNLNS motif modulates viral RNA synthesis and MIB2-mediated signaling - Grace Uwase; Priya Luthra; Olivia A. Vogel; Jyoti Batra; Bruno A. La Rosa; Kathleen C. F. Sheehan; Oam Khatavkar; Jacqueline E. Payton; Robert A. Davey; Nevan J. Krogan; Christopher F. Basler; Daisy W. Leung; et al. (Proceedings of the National Academy of Sciences, 2025)
Ebola virus (EBOV) is a nonsegmented, negative-sense virus (NNSV) with a single-stranded RNA genome. EBOV encodes for a limited number of proteins and thus depends on host factors to facilitate viral replication and pathogenesis. Of the virus-encoded proteins, multifunctional EBOV VP35 (eVP35) is necessary for host immune evasion and viral RNA synthesis. Previous proteomics studies identified an interaction between eVP35 and the host E3 ubiquitin ligase Mindbomb 2 (MIB2). Here, we show how an NNLNS (Asn-Asn-Leu-Asn-Ser) motif (residues 201 to 205) within eVP35 serves as a binding site for MIB2. This motif is critical for eVP35-dependent inhibition of MIB2-mediated interferon induction. It is also important for EBOV RNA synthesis as MIB2 binding to eVP35 inhibited EBOV minigenome activity. Altogether, these findings highlight the importance of the eVP35 protein and the role of host factors in EBOV infection.